Accounting for the slowdown in output growth after the great recession: A wealth preference approach - Kazuma Inagaki; Yoshiyasu Ono; Takayuki Tsuruga (Osaka University, Institute of Social and Economic Research (ISER), 2022)
Previous studies have argued that output growth in advanced economies declined during the Great Recession and remained low afterward. This paper proposes a model to explain this slowdown in output growth. We incorporate wealth preferences and downward nominal wage rigidity into a standard monetary growth model. Our model demonstrates that output initially grows at the same rate as productivity and slows endogenously in the transition path to the stagnation steady state. This stagnation is persistent even if productivity continues to grow at a steady rate. Applying our model to US data, we show that it successfully explains the declines observed in the real interest rate, inflation, and the velocity of money, along with the slowdown in output growth.
Keywords: E41; E47; O10; 330; Secular stagnation; Wealth preferences; Liquidity preferences; the Great Recession; Downward nominal wage rigidity